Understanding the needs of disabled athletes in school: The case of impaired vision athletes - Abd Rahim, Badruel Hairiel; Mohamad Diah, Nurazzura (Institut Penyelidikan Pembangunan Belia Malaysia (IYRES), 2019)
The occurrence of many health problems among women like obesity, cancer and cardio-vascular diseases (CVDs) is associated with their physical inactivity. Often, tight work schedule, misconception of certain practices as well as socio-cultural barriers have become factors for not being actively engaged in any physical activities. Studies show that physical inactivity had become the leading cause of non-communicable diseases (NCDs) among women in many developing countries. This study employs a qualitative approach. Using unstructured interview, this study aims to (1) examine the meaning attached to physical activity among female youth and (2) identify the socio-cultural factors associated with one’s level of physical inactivity. Fifteen Malay female youth aged 18-26 were recruited using the purposive sampling technique. Data were transcribed and analysed using thematic approach. The results of this study reveal that physical activity is a distressful event for female youth. They focused more on other personal obligations compared to physical activities, they are surrounded by physically inactive friends and received minimal parental support. In short, this study believes that becoming physically active among female youth should be considered as one of the core agendas of the nation as well as collective responsibility of the individual, communities and government agencies since maintaining good health in the later lives of women is essential due to women’s longer life expectancy than men.